Nonlinear Bond Model for the Dowel Action considering the Fatigue Damage Effect - Pengfei Li; Ni Tan; Chengzhi Wang (Advances in Materials Science and Engineering)
To investigate the mechanical properties of dowel action under fatigue loads, 3 reinforced concrete specimens with different bar diameters (12 mm, 20 mm, and 25 mm) were subjected to the fatigue loading and were designed to investigate the attenuation character of dowel action and the fatigue failure modes. The load transfer mechanism of the bond was analyzed based on the 3D relative motions between reinforcing bars and subgrade concrete. Fatigue damage effects were considered in the model. A deterioration coefficient based on the deformation path was defined to represent the accumulation of fatigue damage. Verification of the model was conducted by comparing the analysis results with experimental data obtained in this study and from the literature, and satisfactory agreement was obtained.